JURIDICAL STUDY OF BREACH OF LAND SALE (CASE STUDY OF DECISION NUMBER 44/PDT.G/2019/PN KDL) - Angger Restu Basunondo; Fitika Andraini (HERMENEUTIKA : Jurnal Ilmu Hukum, 2023)
The juridical study of default on land sale and purchase Case Study of Decision Number 44/PDT.G/2019/PN KDL and the default dispute in the decision on case Number 44/Pdt.G/2019/PN Kdl between PT Kawasan Industri Kendal and PT. Prospera Jaya. This study uses a qualitative approach which is descriptive analysis with normative juridical methods, namely by using research materials from secondary data collected through library research. The conclusions of this study are (1) Settlement of default disputes in sale and purchase agreements in the decision of Case NUMBER 44/ PDT.G/2019/PN KDL went through a mediation process. By mediating the dispute that occurred between PT Kawasan Industri Kendal as the Plaintiff and PT Prospera Jaya Group as the defendant ended amicably by carrying out several agreements in accordance with applicable law. (2) It is hoped that all companies in Indonesia experiencing civil disputes will first take part in the mediation process. So that in resolving disputes it is not just carrying out the mediation process as a formality to avoid the threat of being null and void, but should resolve disputes in accordance with the objective mediation so that a sense of justice is fulfilled and beneficial to the parties. (3) The researcher advises the general public or companies experiencing default disputes as in Case NUMBER 44/PDT.G/2019/PN KDL to carry out the same process as in the decision of the case. (4) So as to minimize losses between the two parties.